THE IMPACT OF OPERATING MICROSCOPE ON THE OUTCOME OF ENDODONTIC TREATMENT PERFORMED BY POSTGRADUATE STUDENTS - Monea, Monica; Hantoiu, Tudor; Stoica, Alexandra; Sita, Dragos; Sitaru, Alexandru (European Scientific Journal, ESJ, 2015)
Aim of our study. To assess the impact of the operating microscope on the success rate of primary endodontic treatments performed by postgraduate students, during their training program in Endodontics. As null hypotheses we considered that the use of a dental operating microscope in cleaning and shaping the root canals has no statistically significant influence on the treatment outcome in non-surgical treatment of apical periodontitis. Material and methods. We selected a series of 184 consecutively cases of necrotic teeth with chronic periapical lesions that met the inclusion criteria, in which the therapy was performed by postgraduate students or specialists in Endodontics. All patients were treated under the same conditions, regarding materials, techniques and instrumentation. Results. The outcome of the endodontic treatment was assessed based on the recommendations made by the European Society of Endodontics. At 6 months there was a statistical significant difference of the outcomes between study groups (p=0.0151) which became more evident after 18 months (p=0.0078). Conclusions. High-quality endodontic therapy is the basis for long-term clinical and radiological success in endodontic treatment of necrotic teeth. State of the art equipment and thorough knowledge are very important in reaching this goal.